Skrining Kekuatan Genggaman Tangan: Langkah Awal Cegah Sarkopenia untuk Populasi Dewasa di SMP Kalam Kudus - Sim, Alfred Sutrisno; Santoso, Alexander Halim; Destra, Edwin; Putra, Feri Yanto; Felicia, Ivana (Journal of Community Service and Society Empowerment, 2025)
Sarcopenia is a degenerative condition characterized by decreased muscle mass and strength, significantly affecting quality of life and functional ability, especially in the adult and elderly population. This community service activity was conducted at SMP Kalam Kudus, West Jakarta, involving 87 productive age participants. Screening was conducted using handgrip strength measurement, a non-invasive, practical, and effective method for early detection of sarcopenia risk. The results showed that 8.05% of participants had low handgrip strength, indicating an early risk of sarcopenia. Education on the importance of maintaining muscle strength through physical exercise and a healthy lifestyle was provided to participants. Handgrip strength screening has been shown to be an effective early detection tool and can be used as an indicator of chronic disease risk, including stroke. This activity contributes to increasing public awareness of the importance of muscle health and prevention of related complications. Routine implementation of screening and education is expected to improve quality of life and reduce the risk of disability in the adult population.